(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Disasters are natural calamities which takes place accordingly across the world. Recently, in 2020, various disasters took place which affected the world in various scenarios. During these situations, emergency conditions take place which needs to be handled timely and carefully. So, if any technology contributes to these situations, proves to be a “Boon” for the world. To improve the performance of a vehicle designing is the important aspect for it. At the point when the vehicle runs over a channel at a fast pace, the medium will go along the vehicle in term of obstruction. The reason behind the vehicle going in the opposite direction, when the vehicle moves in at high velocity is because of the structure of the room as there is air space density inside the room. Other than that, the blueprint of the vehicle ought to have an air of fascination with individuals who look at everything about plan as far as inventiveness and aesthetical worth. The land and/or water capable automobile is a double reason vehicle which is described by velocity and intangibility on water, potability, and adaptability ashore and exceptional traffic flow capacity at the intersection of land and water. This project aims to make an Arduino based boat cum car which can highly contribute to disasters. The project would work both as a boat on one side and as a car on other side. These technologies can help people in various ways, for example, rescue operations, essentials delivery, roads having large distance than water and many more. People can use this technology according to the requirement, as a boat or as a car, as and when required.